Fatores que influenciam a escolha do modo de transporte para trabalho em cidades de pequeno porte: estudo de caso Cedral - SP - Castro, Vinicius Renan Fujino (2019)
Urban mobility is one of the pillars for the sustainable development of cities. However, as a result of the lack of a strategic planning that considers the different transport systems, the saturation of the cities has contributed to the general limitation of mobility. Thus, it is noted that these problems are not restricted to large cities, but are also a reality in small ones (with up to 20 thousand inhabitants). In this context, this research proposed to carry out an investigation about the factors that influence the option for a mode of transport for trips to work in a small city. The methodology used was based on data collection by questionnaires where the factors influencing the decisions of the individuals on the choice of foot, bicycle, motorcycle and car modes for journeys to work were identified. The results indicated that the factors related to the health aspects, comfort, chances of being involved in accidents, chances of being assaulted, economy, being bothered by sun and rain, difficulty finding parking space and environment influence the decisions of individuals.